(untitled) - Canfield, Jack (Cos Cob, CT., 2012)
Being a teen is hard - but you are not alone. This book is filled with stories that will make you laugh and make you cry. It will act as a best friend, keep you company, motivate you, and reassure you that other teenagers have been through the same ups and downs and have come out okay.
Keywords: Teenagers,Thanh thiếu niên; Conduct of life,Ứng xử trongcuộc sống